Development Of Project-Based E-Modules For Sociology Curriculum Study - Suryanti, Ni Made Novi; Nursaptini, Nursaptini; Wahidah, Ananda (Journal of Classroom Action Research, 2024)
A This study aims to develop and find out the effectiveness of project-based E-modules for students of the FKIP Sociology Education Study Program. This development research uses a 4D model, namely define, design, develop, and disseminate. The results showed that e-modules are one of the teaching materials that can support student learning independence both in online and offline learning. The results of the validity test show that the e-module developed shows a valid category because it is in internal 2.5<SR£3.5. The e-module has also met the practicality test because the average score obtained is internal 2.5<SR£3.5. The output score obtained at the N-Gain Score of 0.52 in the internal range of 0.3£g£0.7 refers to the medium category which shows that the e-module developed is effective in improving student learning outcomes.